FAO species catalogue : - Allen, George Rollason (Food and Agriculture Organization of the United Nations, 1985)
It provides a comprehensive key to genera and species, preceeded by an illustrated glossary of technical terms and measurements. The systematic part of the catalogue includes a drawing and a distribution map for each species, a list of scientific and vernacular species names and 1wide-ranging information on habitat, bioloy, and fisheries.